A School-Based Aerobic Exercise Program to Improve Blood Sugar Levels Among Adolescents at Risk of Type 2 Diabetes - Susy Puspasari; Sofiah Sri Amalia (STIKep PPNI Jawa Barat, 2025)
Background: The prevalence of type 2 diabetes mellitus (T2DM) continues to increase among adolescents due to sedentary lifestyles and poor health behaviors. Early preventive interventions, particularly physical activity integrated into school settings, are essential to minimize the risk of future metabolic disorders. This study aimed to determine the effect of a school-based aerobic exercise program on blood sugar levels among adolescents at risk of T2DM. Methods: A quasi-experimental pre-test and post-test control group design was conducted among 60 adolescents aged 13–15 years in Bandung City who were identified as having moderate to high diabetes risk using the FRIDEM application. Participants were assigned into an intervention group (n = 30) and control group (n = 30). The intervention group performed structured aerobic exercise for 30 minutes, three times per week over four weeks, while the control group followed their usual school routine. Fasting blood glucose was measured before and after the intervention. Data were analyzed using paired t-test and ANCOVA. Results: There was a significant decrease in fasting blood glucose in the intervention group from 123.00 ± 15.70 mg/dL to 100.97 ± 10.80 mg/dL (p < 0.001). In contrast, the control group showed a slight increase from 110.77 ± 14.12 mg/dL to 115.70 ± 17.55 mg/dL (p = 0.077). ANCOVA indicated a significant difference in post-test blood glucose values between groups after controlling for baseline levels (p < 0.001). Conclusion: A structured school-based aerobic exercise program effectively reduced blood sugar levels among adolescents at risk for type 2 diabetes mellitus. Incorporating regular aerobic exercise into school curricula may serve as an important preventive strategy to improve metabolic health and reduce diabetes risk in youth.